2011
DOI: 10.1016/j.aller.2010.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between cytokine levels in nasal fluid and eosinophil counts in nasal polyp tissue in asthmatic and non-asthmatic patients

Abstract: Our results showed that these patients with similar clinical findings had significantly different mediator profiles in their nasal secretions, implying clear differences in pathogenesis of their NP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
10
0
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 23 publications
5
10
0
6
Order By: Relevance
“…IL-6 plays a significant role as a local inflammatory mediator in CRS. 10 Nasal fluid from 30 CRS with NP (CRSwNP) patients showed a positive correlation between expressed elevated IL-6 and eosinophilia in their NP tissue. Sachse et al went further to report that intracellular S. aureus located in the epithelial layer of NPs could strongly induce IL-6 expression.…”
mentioning
confidence: 99%
“…IL-6 plays a significant role as a local inflammatory mediator in CRS. 10 Nasal fluid from 30 CRS with NP (CRSwNP) patients showed a positive correlation between expressed elevated IL-6 and eosinophilia in their NP tissue. Sachse et al went further to report that intracellular S. aureus located in the epithelial layer of NPs could strongly induce IL-6 expression.…”
mentioning
confidence: 99%
“…Most histological studies of nasal polyp have been performed in Caucasian patients and data from Asian population is still lacking. The majority was found to be eosinophil-predominant, comprising 73-92.5% (Armengot et al 2010; interleukin-8, which is an important chemo-attractant of neutrophil, and size of nasal polyps (Wen et al 2012;Majima 2004), while it showed poor therapeutic efficacy and worse clinical response in eosinophilic NP (Haruna et al 2009;Peric et al 2011). By understanding the histological types of the NP, it would provide us certain prognostic information and allow specific tailored treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Drveni štapić sa vatom na vrhu (deo sa vatom je dužine oko 10 mm, a širine oko 4 mm), tokom prednje rinoskopije postavlja se što bliže ili se drži u srednjem nosnom hodniku tokom 60 sekundi, koliko je potrebno da se komadić vate natopi nosnim sekretom (slika 2). Zatim se deo štapića sa vatom na vrhu odlomi i ubaci u ependorf epruvetu u kojoj se nalazi transfer-medijum (18)(19)(20)(21)(22)(23).…”
Section: ) Apsorpcione Tehnikeunclassified
“…Pošto se uzme uzorak nosnog sekreta, on se unosi u ependorf epruvetu u kojoj se nalazi 1 ml "transfer medijuma" (18)(19)(20)(21)(22)(23). To je fosfatno puferisani fiziološki rastvor sa 50 μg/ml gentamicina, 340 μg/ml penicilina G i 500 μg/ml fungizona, koji služe kao konzervansi i sprečavaju razmnožavanja bakterijskih i gljivičnih mikroorganizama u uzorku (18)(19)(20)(21)(22)(23). U "transfer medijumu" uzorak stoji minimalno 30 minuta, koliko je potrebno za difuziju citokina/hemokina iz uzorka sekreta, koji je hiperosmolalan u "transfer medijum", koji je hipoosmolalan.…”
Section: Merenje Protočnom Citometrijomunclassified
See 1 more Smart Citation